1988
DOI: 10.1159/000125015
|View full text |Cite
|
Sign up to set email alerts
|

Differential Angiotensin-Converting Enzyme Inhibition in Brain after Oral Administration of Perindopril Demonstrated by Quantitative in vitro Autoradiography

Abstract: To help elucidate potential sites for the central actions of a new angiotensin-converting enzyme (ACE) inhibitor, perindopril, ACE levels were measured in the brain of Sprague-Dawley rats by quantitative in vitro autoradiography after administration of the drug. Following acute oral administration of 1 mg/kg perindopril, ACE in the two circumventricular organs, the subfornical organ and organum vasculosum of the lamina terminalis, was markedly inhibited and had only partially recovered after 24 h. The ACE inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 5 publications
2
10
0
Order By: Relevance
“…Studies with the ACE inhibitor ceronapril showed no inhibition of brain ACE, but inhibition in the circumventricular organs, with results after 2 weeks of chronic dosing being essentially the same as those obtained after a single dose [24]. However, large doses of perindopril (up to 16 mg/kg) did progressively inhibit ACE in brain structures, including the basal ganglia [25]. Given that vasopeptidase inhibitors will be used for long periods of time clinically, further studies are needed in order to assess more precisely their effects on cellular structures within the brain and outside the blood-brain barrier.…”
Section: Discussionmentioning
confidence: 77%
“…Studies with the ACE inhibitor ceronapril showed no inhibition of brain ACE, but inhibition in the circumventricular organs, with results after 2 weeks of chronic dosing being essentially the same as those obtained after a single dose [24]. However, large doses of perindopril (up to 16 mg/kg) did progressively inhibit ACE in brain structures, including the basal ganglia [25]. Given that vasopeptidase inhibitors will be used for long periods of time clinically, further studies are needed in order to assess more precisely their effects on cellular structures within the brain and outside the blood-brain barrier.…”
Section: Discussionmentioning
confidence: 77%
“…36 It is proposed that due to the high concentration of the enzyme in this area, 36 the activity of ACE is not effectively blocked by this dose of perindopril, allowing local conversion of Ang I to II and potent stimulation of drinking. 37 It has also been noted that rats treated long term with an AT-1 receptor antagonist have increased urinary volume and increased water intake.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, they cross the blood-brain barrier (Evered et al, 1980;Sakaguchi et al, 1988;Sica, 2003) and reduce the levels of AII. Because AII induces striatal DA release, acute administration of ACEIs, such as Captopril, inhibits DA neurotransmission in the central nervous system (Jenkins et al, 1997;Tsuda et al, 1998).…”
mentioning
confidence: 99%